2014
DOI: 10.1002/ejoc.201402538
|View full text |Cite
|
Sign up to set email alerts
|

Iodine‐Mediated Oxidation of Ynamides: A Facile Access to N‐Monosubstituted α‐Ketoamides and α‐Ketoimides

Abstract: An efficient iodine‐mediated oxidation reaction for ynamides has been developed to produce N‐monosubstituted α‐ketoamides and α‐ketoimides. This oxidative method, which exhibits good functional group tolerance, was performed under mild conditions without a metal catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 87 publications
1
9
0
1
Order By: Relevance
“…An ynamide without the ester moiety, N ‐benzyl‐4‐methyl‐ N ‐(phenylethynyl)benzenesulfonamide ( 7 a ), accomplished the synthesis of α‐keto amide 7 aa in 89 % yield under open air conditions. In this case, we believe that p ‐tolylsulfenylchloride probably plays the role of a Lewis acid like iodine (Scheme , I) . We also confirmed that, in the presence of radical scavengers like TEMPO and BHT, the cyclization proceeded smoothly to form oxazolidine‐2,4‐dione 2 a in 65 and 69 % yields, which strongly rules out a radical process (Scheme , II) .…”
Section: Resultssupporting
confidence: 69%
“…An ynamide without the ester moiety, N ‐benzyl‐4‐methyl‐ N ‐(phenylethynyl)benzenesulfonamide ( 7 a ), accomplished the synthesis of α‐keto amide 7 aa in 89 % yield under open air conditions. In this case, we believe that p ‐tolylsulfenylchloride probably plays the role of a Lewis acid like iodine (Scheme , I) . We also confirmed that, in the presence of radical scavengers like TEMPO and BHT, the cyclization proceeded smoothly to form oxazolidine‐2,4‐dione 2 a in 65 and 69 % yields, which strongly rules out a radical process (Scheme , II) .…”
Section: Resultssupporting
confidence: 69%
“…Several reports described the oxidation of ynamides to produce α-ketoimides by using expensive transition-metal catalysts, external oxidants, and harsh conditions that restricted the practical applicability of the methods . In this context, Zhu and co-workers disclosed the validity of N -Boc-ynamides as convenient starting materials for the preparation of N -monosubstituted α-ketoamides upon exposure to the inexpensive ecofriendly iodine/water/air oxidant system in the presence of TFA as an additive. Thus, the N -Boc-ynamides were easily prepared by coupling N -Boc-benzylamines or N -Boc-anilines with terminal alkynes, including alkylacetylenes, via the corresponding bromoethynyl derivatives, according to a reported procedure. , …”
Section: Amidation Approachesmentioning
confidence: 99%
“…To date, a plethora of synthetic methods have been reported to be capable of affording α‐ketoamide scaffolds. For instance, the oxidation on pre‐functionalized precursors such as hydroxyl amides, haloamides or aminoamides; the amidation of α‐ketoacids or acyl chlorides, the C‐H amidation of α‐ketoaldehydes, the oxoamidation of simple aldehydes and ketones, the oxoamidation of α‐hydroxyl or ester functionalized ketones, the aminocarbonylation reaction using isocyanides, the oxidative oxoamidation of α,α‐dihaloketones, the oxoamination reactions based on the cleavage of C‐C single bonds, C=C double bond and C≡C triple bonds, and others …”
Section: Introductionmentioning
confidence: 99%